114 Association of Trunk Muscle Function with Gait Ability of Patients with Lumbar Spinal Canal Stenosis. (20th December 2019) - Shintani, Takeshi; Otsuki, Shingo; Hashimoto, Masashi; Tagashira, Satoshi; Kinoshita, Kazuaki
Abstract: Introduction: Lumbar spinal canal stenosis (LSCS) is not always correlated with spinal stenosis and severity of clinical symptoms. Although, it is important for trunk muscle function to enhance the dynamic stability of the lumbar spine, however few studies have reported on this. We hypothesized that trunk muscle function and gait ability of LSCS patients are related. This study aimed to clarify the association between trunk muscle function, using Side Bridge test (SB), and gait ability of LSCS patients. Methods: The subjects were 42 patients with LSCS: 17 supported the trunk by the foot (F-group), and 25 supported the trunk by the knee (K-group) in the SB test. The SB test was performed to determine the posture holding time. Gait ability was evaluated by measuring the time of 10-m walk test (10MWT) preoperatively and 2 weeks postoperatively. The 2 weeks postoperative 10MWT was divided by the preoperative 10MWT to calculate the 10MWT change rate. The contents of this study were the relation between SB test and preoperative 10MWT, SB test and 10MWT change rate in each group. Moreover, the median value of SB test was calculated for both groups; based on these values, the patients were categorized into high-value and low-value groups. Differences between the 10MWT and 10MWT change rates of both groups were examined using Mann-Whitney U-test. Results: There was a significant correlation between SB test and 10MWT (F-group: r=-0.63, p=0.004; K-group: r=-0.59, p = 0.002), 10 MWT change rate (F-group: r=-0.59, p=0.01; K-group: r=-0.41, p=0.04). With respect to the 10MWT, the high-value group was significantly faster than the low-value group (F-group: p=0.02, K-group: p=0.03), and with respect to the 10MWT change rate, the high-value group was significantly better than the low-value group (F-group: p=0.02, K-group: p=0.01). Conclusion: Trunk muscle function is associated with gait ability of LSCS patients.